2020
DOI: 10.1093/mnras/staa1778
|View full text |Cite
|
Sign up to set email alerts
|

Formation of aqua planets with water of nebular origin: effects of water enrichment on the structure and mass of captured atmospheres of terrestrial planets

Abstract: ABSTRACT Recent detection of exoplanets with Earth-like insolation attracts growing interest in how common Earth-like aqua planets are beyond the Solar system. While terrestrial planets are often assumed to capture icy or water-rich planetesimals, a primordial atmosphere of nebular origin itself can produce water through oxidation of the atmospheric hydrogen with oxidizing minerals from incoming planetesimals or the magma ocean. Thermodynamically, normal oxygen b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…One should also note that the production of nebula-based water depend on the nebula properties such as the dust grain depletion factor, etc. (Lammer et al, 2014;Kimura and Ikoma, 2020), which can be different on other star systems. Recently, Kimura and Ikoma (2020) showed that primordial atmospheres could be highly enriched in water vapor, if one does not assume solar abundances for the gas disk properties.…”
Section: Figmentioning
confidence: 96%
“…One should also note that the production of nebula-based water depend on the nebula properties such as the dust grain depletion factor, etc. (Lammer et al, 2014;Kimura and Ikoma, 2020), which can be different on other star systems. Recently, Kimura and Ikoma (2020) showed that primordial atmospheres could be highly enriched in water vapor, if one does not assume solar abundances for the gas disk properties.…”
Section: Figmentioning
confidence: 96%
“…In global chemical equilibrium, mantle oxygen may be able to produce water in mole number comparable to or more than hydrogen (Schlichting & Young 2021). Thus, primordial H/He atmospheres may be enriched with water vapour (Kimura & Ikoma 2020). In consequence, the water will in large parts dissolve into the mantle.…”
Section: Discussionmentioning
confidence: 99%
“…For now, there is no comprehensive interior model that accurately accounts for the chemical reactive atmospheremagma ocean boundary as well as the partitioning of water and other volatiles in the deep interior of sub-Neptunes. Only few studies have investigated individual aspects of it Lichtenberg 2021;Schlichting & Young 2021;Vazan et al 2020;Kimura & Ikoma 2020;Olson & Sharp 2018;Chachan & Stevenson 2018). As volatile partitioning in the deep interior has been neglected for inference studies of exoplanets, previous interior predictions have thus far generally underestimated the amount of water and hydrogen for sub-Neptunes.…”
Section: Discussionmentioning
confidence: 99%
“…(right panel ) migration. Here we have carried out those calculations by adding the effects of atmospheric accumulation and loss (Kimura and Ikoma, 2020) in the population synthesis models (Miguel et al, 2019). The symbols for radii of 1-4 R ⊕ are shown with different colours and sizes, indicating that the highdensity planets are diverse in bulk composition; namely, they have different ice-to-rock ratios and different atmospheric masses.…”
Section: Compositional Signatures Of Different Formation Regionsmentioning
confidence: 99%